KERAGAAN PRODUKSI DAN HARGA KENTANG DI KECAMATAN PANGALENGAN, KABUPATEN BANDUNG - Salma Aulia Rahmah; Eliana Wulandari (Universitas Galuh Ciamis, 2020)
Agriculture has an important role in food security in Indonesia from micro to macro level. One of the agricultural subsectors is horticulture particularly in potato that can support food diversification programs in Indonesia. The problem that occurs in horticultural commodities is the fluctuating selling prices that affect the economic benefits received by business actors. This study aims to analyze the revenue of potato farmers from 2016 to 2018. The research was conducted in Pangalengan Sub District by including 52 potato farmers. The data in this study used both primary and secondary data, which were then analyzed quantitatively. The results of the study showed that the average amount of potato production in 2016 to 2018 in Pangalengan Sub District was 17.27 tons per hectare, while the average price of potatos in the last three years was Rp. 7,640 per kg. Based on the results of the study, the average of potato revenues in 2016 - 2018 is Rp. 131.946.193 per hectare. Revenue of potato farmers in Pangalengan Sub District is quite large, thus potato farmers have the potential to earn large profits if they can reduce production costs.